Transcriptome and Proteome Studies Reveal Candidate Attachment Genes during the Development of the Barnacle Amphibalanus Amphitrite - Al-Aqeel, Sarah; Ryu, Taewoo; Zhang, Huoming; Chandramouli, Kondethimmanahalli H.; Ravasi, Timothy (Frontiers in Marine Science, 2016)
The acorn barnacle, Balanus amphitrite, is the main biofouling organism in marine environments. In the present study we profiled the transcriptome and proteome of B. amphitrite at different life stages (nauplius II, nauplius VI and cyprid) from the Red Sea, where the average water surface temperature is 34°C and the salinity reaches 41‰. We identified 65,784 expressed contigs, and a total of 1,387 expressed proteins measured by quantitative proteomics. We found that osmotic stress, salt stress, hyperosmotic response and the Wnt signaling pathway were strongly up-regulated during the planktonic stage, while the MAPK pathway, lipid metabolism, and cuticle development genes were down-regulated. In the transition stage between the nauplius VI and the cyprid, genes that are involved in blood coagulation, cuticle development and eggshell formation were highly up-regulated, while the nitric oxide pathway, which stimulates the swimming and feeding response in marine invertebrates, was down-regulated. We are able to report for the first time that sound sensory system proteins are highly abundant in the nauplius VI stage, implying that these proteins are good targets for the development of new antifouling compounds. The results presented here together with the new genome-wide datasets for a non-model specie represent an important resource for the study of biofouling and development.